Effectiveness of Power flow by Shunt Compensation on Power Transmission (International Journal of Engineering and Computer Science, 2014)
This paper is to develop a program to determine the required shunt compensation and after which,conduct power system analysis using simulation to evalute load voltage at fixed sending end voltage.The purpose of reactive power compensation is to change electrical characteristic of transmission line and make more compatible with load demand. The effect of change in length of transmission line on voltage profile is analyzed. This paper presents an analysis of the effect of shunt compensation level on the line voltage profile, transfered power capability, power factor and transmission losses. For this purpose simple model is developed to calculate the shunt compensated transmission line load voltage. The model is designed and simulated using MATLAB. The results show the effectiveness of shunt compensation on power transmission. It gives basic mechanism of shunt compensation, also highlight its benefits for power system.